The effect of financial inclusion and competitiveness on financial stability: Why financial regulation matters in developing countries? - Jo\~ao Jungo; Mara Madaleno; Anabela Botelho (Journal of Risk and Financial Management, 2022)
This study aims to assess the effect of financial inclusion and competitiveness on banks' financial stability, considering the moderating role of financial regulation. To do so, we compare the effects of these variables in Sub-Saharan African (SSA) and Latin American and Caribbean (LAC) countries. Our results suggest that inclusion enhances bank stability in SSA and LAC countries, and financial regulation contributes to increasing financial stability in LAC countries, while we find no statistical significance in the effect of financial regulation on financial stability in SSA countries. Moreover, competitiveness negatively impacts financial stability, and financial regulation moderates the negative effect of competitiveness on financial stability in SSA and LAC countries. We also find that financial inclusion reduces credit risk in SSA countries, and for LAC countries financial inclusion increases credit risk and reduces bank profitability. Regarding the practical implications, this study shows that fostering financial inclusion in the countries under study contributes significantly to improving the welfare of households and especially to the stability of the financial system. The present study allows expanding of the scarce literature by examining the effect of financial inclusion and market structure on financial stability in two different samples, consisting of 41 countries in the SSA region and 31 countries in the LAC region, throughout 2005-2018.
Keywords: 330; financial inclusion; financial stability; competitiveness; financial regulation